In Search of a New Paradigm for Functional Magnetic Resonance Experimentation With Language - Arantes, Maria Eugênia; Cendes, Fernando (Frontiers in Neurology, 2020)
Human language can convey a broad range of entities and relationships through processes that are highly complex and structured. All of these processes are happening somewhere inside our brains, and one way of precising these locations is through the usage of the functional magnetic resonance imaging. The great obstacle when experimenting with complex processes, however, is the need to control them while still having data that are representative of reality. When it comes to language, an interactional phenomenon in its nature, and that integrates a wide range of processes, a question emerges concerning how compatible it is with the current experimental methodology, and how much of it is lost in order to fit the controlled experimental environment. Because of its particularities, the fMRI technique imposes several limitations to the expression of language during experimentation. This paper discusses the different conceptions of language as a research object, the hardships of combining this object with the requirements of fMRI, and what are the current perspectives for this field of research.